Business Strategy Formulation UD. Reza Jaya - Muhammad Syafri Syafreza Hasyim; Sri Hartini; Muh Rezky Pangeran (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
This study aims to identify strategic positions through Internal and External (IE) analysis at UD. Reza Jaya and Formulate what business strategy should be carried out by UD. Reza Jaya to be able to win the business competition. This study uses a quantitative approach with descriptive analysis. The location of research was carried out at the Building Store, UD. Reza Jaya Besur Village, Sekaran District, Lamongan Regency. The research was used from April-May 2023. The data collection method is by making a reservation or studying directly on the research object. The data used are interviews and secondary data documentation. SWOT analysis is used for the advantages and disadvantages of UD. Reza Jaya, both internally and externally. The results showed that internal and external factors indicated the position of UD. Reza Jaya is currently in quadrant I, namely, showing the "grow and build" position. And the SWOT analysis produces eight alternative strategies with specifications through SO, WO, ST, and WT strategies. Proposed improvement priorities used to improve the company's business processes can be carried out by applying the concept of the Business Model Canvas. The results of the QSPM analysis show the formulation of the most likely alternative strategy to be carried out by UD. Reza Jaya is a Product Development Strategy with the highest score of 11.80000. While the second alternative, namely the horizontal integration strategy, only gets a value of 10.37000